The paradox of drug taking: The role of the aversive effects of drugs - Riley, Anthony L. (Physiology & behavior, 2011)
In 1991, Woods described the paradoxical nature of eating, specifically, that it produced aversive and negative effects. He noted in this analysis the multiple physiological and behavior adaptations, both learned and unlearned, that were aimed at regulating food intake and reducing its aversive, disruptive effects. From this position, he argued that consumption reflected a balance of the positive and aversive effects of eating. The present review extends this analysis to drug use and abuse, i.e., that drug taking itself also is a balance of reward and aversion. Although traditionally the analysis of drug use and abuse has focused on a drug's positive and negative rewarding effects, the present review highlights the aversive effects of these same drugs, e.g., cocaine, morphine, alcohol, and describes such effects as protective in nature. This balance and the manner by which it can be impacted by subject and experiential factors are described with a focus on genetic models of drug abuse using the Lewis and Fischer inbred rat strains. ▶ Relationship between food consumption and drug abuse. ▶ Balance of reward and aversion in drug use and abuse. ▶ Strain differences in aversion learning as models of drug abuse. ▶ Epigenetic modulation of genetic phenotypes.